Study of Composite Fiber Reinforcement of Cracked Thin-Walled Pressure Vessels Utilizing Multi-Scaling Technique Based on Extended Finite Element Method - Mirmohammad, S.H.; Safarabadi, M.; Karimpour, M.; Aliha, M.R.M.; Berto, F. (Проблемы прочности, 2018)
One of the most important challenges of storing fluids in thin walled pressure vessels under internal pressure is preventing crack propagation. In low temperature, steel shows brittle crack propagation characteristic which is highly dangerous. In this paper, a new numerical model is presented in order to investigate the reinforcement of a cracked thin walled pressure vessel by composite patch. Одна из наиболее важных проблем хранения жидкостей в тонкостенных сосудах высокого давления предотвращение распространения трещин. При низких температурах имеет место хрупкое распространение трещин, которое является опасным. Представлена новая численная модель расчета усиления тонкостенного сосуда давления с трещиной композитной накладкой. Однією з найбільш важливих проблем зберігання рідини в тонкостінних посудинах високого тиску є запобігання розповсюдженню тріщин. При низьких температурах має місце крихке розповсюдження тріщин, що є небезпечним. Представлено нову числову модель розрахунку підсилення тонкостінної посудини тиску з тріщиною композитною накладкою.